(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This study explores the impacts of women academics on the advancement of tertiary education. Utilizing secondary data from both print and online sources, the research underscores the substantial contributions made by women academics in Nigerian tertiary institutions which include among others; teaching, research, community service, and the provision of effective leadership. However, the paper highlights obstacles such as inadequate implementation of gender policies, limited representation of women academics, institutional weaknesses, culture, religion, early marriage and patriarchy, all of which hinder the optimal engagement of women academics in tertiary institutions. In light of these findings, the study recommends affording women academics increased opportunities for responsibilities and leadership roles to further enhance their contributions.